Some aspects of combine harvester's technological adjustment task's solving is carrying out on the basis of fuzzy logic conclusion - L.V. Borisova (Advanced Engineering Research, 2009)
One of the combine harvester's working organs technological adjustment task solving on the base of fuzzy logic is considered.